(3QSGdI aj GdfaSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SCd HYV GdQDSGA SeJg GdYGdjI Cf GdfaS GdfGWbI LhgQ Ce YQV hGfgG hEf cGfJ LhgQ agd JHbi EfJbGV bGdHgG Ce jJdGTi ef EfJaGVI s
(3BNQgG (B:s
(3deG gh HYO GdehJ hCf jQaV efg GddPGJ GdLSOGfjI eG jecf QaVgG djUjQ faSg eaGQbkG dbGdHgG ai JMbjb GdHbGA GdOGFe hPdc eG CQOfG Cf fHjf hHGddg GdJhajb hGdMeO dhGgH GdgGOjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B896s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdadSaI hGdefWbs